2022
DOI: 10.18295/squmj.6.2021.087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Peer Education on the Hope of Patients with Thalassaemia Major

Abstract: Objective: Thalassemia major (TM) is one of the most common chronic genetic disorders in today’s world. The psychological impacts of this disease can affect patients’ hopes. Considering the positive role and importance of suitable educational methods, the aim of this study was to determine the effect of peer education on the hope of patients with TM. Methods: This was a quasi-experimental single-group study performed on 50 patients with TM undergoing treatment in Zabol in 2020. Patients were recruited by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The results of the study by Gholamzadeh and colleagues (2022) showed that the hope of patients undergoing Percutaneous Coronary Intervention (PCI) in the intervention group (education using multimedia) compared to the control group (education using pamphlets) in one and Two weeks after the intervention, it increased signi cantly (88). Also, in the study of Seyedoshohadaee et al (2021), the results showed that the average hope scores of patients with thalassemia major increased signi cantly after receiving self-care training by the peer group compared to before the training (P=0.028) (89); The results of Bahmanpour et al's study (2023) showed that telenursing led to a signi cant increase in the hope of mothers with premature babies in the intervention group (receiving education through telenursing) compared to the control group (not receiving training) (P<0.05) (90).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study by Gholamzadeh and colleagues (2022) showed that the hope of patients undergoing Percutaneous Coronary Intervention (PCI) in the intervention group (education using multimedia) compared to the control group (education using pamphlets) in one and Two weeks after the intervention, it increased signi cantly (88). Also, in the study of Seyedoshohadaee et al (2021), the results showed that the average hope scores of patients with thalassemia major increased signi cantly after receiving self-care training by the peer group compared to before the training (P=0.028) (89); The results of Bahmanpour et al's study (2023) showed that telenursing led to a signi cant increase in the hope of mothers with premature babies in the intervention group (receiving education through telenursing) compared to the control group (not receiving training) (P<0.05) (90).…”
Section: Discussionmentioning
confidence: 99%